Marketing - Kerin, Roger A.; Hartley, Steven William; Berkowitz, Eric N.; Rudelius, William (New York McGraw-Hill, 2006)
Contains the KMT Marketing Planning Software. This commercial software contains planning templates with guidance provided for each section of the plan, and includes a marketing plan as an example. It operates within the Microsoft Office Suite, so students work directly in Word and Excel to create professional looking documents.
Include Illustrations, Glossary and Indexes.
Keywords: Marketing -- Canada